Gestión de la comunicación gubernamental intercultural dirigida a pueblos indígenas en el marco de la COVID-19 - Mier y Teran Moscoso, Ruth Maria (2021)
This thesis explores the particular characteristics of intercultural government communication directed to indigenous peoples in the context of COVID-19. For this, it develops the theoretical framework of the concepts of interculturality and government communication, identifying criteria for its practical application. Then, presents a case study in an intervention on gubernamental and intercultural communication by the Ministry of Culture of Peru, addressed to indigenous population. As a result of the research, innovative strategies are identified, such as the work of intercultural indigenous promoters that allow the State to establish a horizontal dialogue with indigenous peoples.